ENDOSONOGRAPHY VERSUS ENDOSCOPIC RETROGRADE CHOLANGIOPANCREATOGRAPHY IN DIAGNOSING EXTRAHEPATIC BILIARY OBSTRUCTION - Tozzi di Angelo, Igor; Prochazka, Vlastimil; Holinka, Martin; Zapletalova, Jana (Biomedical papers, 2011)
Objective: Endosonography (EUS) performed prior to endoscopic retrograde cholangiopancreatography (ERCP) or surgery in patients with a low to moderate probability of choledocholithiasis can reduce morbidity, mortality and costs.Aims: This study aimed at evaluating the sensitivity and specificity of EUS and transabdominal ultrasonography (TUS) compared to ERCP in a cohort of 100 patients diagnosed with extrahepatic biliary obstruction.Methods: There were four working groups. The first group processed the initial data including history, physical examination and assessment of laboratory markers of cholestasis. The second group examined TUS. The third group examined the pancreas and biliary tree using EUS, always prior to ERCP. The fourth working group carried out ERCP.Results: The sensitivity and accuracy of EUS in the diagnosis of common bile duct dilatation were 84% and 83%, respectively, i.e. significantly higher (p=0.0001) than TUS (46% and 66%, respectively). The specificities of methods (82%, 91%) were not significantly different (p=0.218). The sensitivity and accuracy of EUS in the diagnosis of pathological content of the common bile duct were 88% and 92%, respectively, i.e. significantly higher (p
Keywords: Radial endosonography/Endoscopic retrograde cholangiopancreatography/Transabdominal ultrasonography/Choledocholithiasis